Perspektif Siswa MTs Yasim Nata Pada Penerapan Blended Learning di Masa Pandemi Covid-19 - Yeni Rahmawati; Muh. Irfan; Nur Islamiati (Jurnal LENTERA: Jurnal Studi Pendidikan, 2022)
This study aims to describe the perspective of MTs Yasim Nata students on the application of blended learning during the covid-19 pandemic. The approach used is qualitative and quantitative with a descriptive type. The subject of this research is one teacher and 27 students at MTs Yasim Nata. Data collection techniques in this study are through interviews and the distribution of questionnaires or questionnaires. The results showed that the use of the blended learning method was measured using 5 aspects, namely: 1) Aspects of student learning motivation using Blended Learning obtained the highest average score of 4.2 with the alternative answers strongly agreeing; 2) Aspects of student learning activities using Blended learning get an average value of 4.2 with the alternative answers agree; 3) Aspects of a conducive learning process using Blended Learning have alternative answers that strongly agree with the acquisition of 3.5 as the average value; 4) Aspects of mastery of the material by students using Blended learning obtained an average value of 4.5 with alternative answers strongly agree; 5) Aspects of student learning outcomes using Blended Learning have an average value of 3 where students choose alternative answers that strongly agree.